Investigations at the Epigravettian site of Barmaky in Volhynia, north-west Ukraine: analyses and taxonomic reflections Untersuchungen am Epigravettien-Fundplatz Barmaky in Volhynia, Nordwest-Ukraine: Analysen und taxonomische Überlegungen - Chabai, Victor; Dudnyk, Diana; Pasda, Kerstin; Brandl, Michael; Maier, Andreas (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2022)
Known since 1981 and investigated in several campaigns between 1982 and 2007, the site of Barmaky in northwest Ukraine has recently been the subject of renewed investigations from 2018 to 2020. The assemblage is strikingly similar to the one reported from the famous site of Mizyn, located at a distance of about 490 km to the east, except for the absence of a mammoth bone structure. With a weighted average of radiocarbon dates of 19,004 ± 60 calBP, Barmaky is the so far oldest site in north-west Ukraine after the hiatus of the Last Glacial Maximum. The early chronological and – compared to other Epigravettian sites – rather remote spatial position of the site raise several questions, for instance regarding the taxonomic attribution or the role in the resettlement process of the mid-northern latitudes after the Last Glacial Maximum. In this paper, we address these questions in light of the current state of knowledge on the stratigraphy, spatial organisation, faunal assemblage as well as lithic typology and technology. Due to the circumstances since 2020 (pandemic and war), not all analysis could be completed, and some results must still be considered preliminary.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Eastern Europe; Epigravettian; taxonomy; technology; typology